Recent advancements in molecular photoacoustic tomography - Eric Hall; Chengyun Tang; Lei Li (JPhys Photonics)
Photoacoustic tomography (PAT) is an emerging biomedical imaging technology that combines the molecular sensitivity of optical imaging with the spatial resolution of ultrasonic imaging in deep tissue. Molecular PAT, a subset of PAT, takes advantage of the specific absorption of molecules to reveal tissue structures, functions, and dynamics. Thanks to the high sensitivity to the optical absorption of molecules, PAT can selectively image those molecules by tuning the excitation wavelength to each target’s optical absorption signature. PAT has imaged various molecular targets in vivo , ranging from endogenous chromophores, e.g. hemoglobin, melanin, and lipids, to specialized exogenous contrasts such as organic dyes, genetically encoded proteins, and nano/microparticles. Each molecular contrast hosts inherent advantages. Endogenous contrasts allow for truly noninvasive imaging but cannot attain high specificity or sensitivity for many biological processes, whereas artificial exogenous contrasts can. Recent advances in imaging these contrast agents have shown the immense potential of photoacoustic imaging for diagnosing, monitoring, and treating medical conditions, along with studying the fundamental processes in vivo .